Monolithic Friction and Contact Handling for Rigid Bodies and Fluids Using SPH. (20th January 2023) - Probst, T.; Teschner, M.
Abstract: We propose a novel monolithic pure SPH formulation to simulate fluids strongly coupled with rigid bodies. This includes fluid incompressibility, fluid–rigid interface handling and rigid–rigid contact handling with a viable implicit particle‐based dry friction formulation. The resulting global system is solved using a new accelerated solver implementation that outperforms existing fluid and coupled rigid–fluid simulation approaches. We compare results of our simulation method to analytical solutions, show performance evaluations of our solver and present a variety of new and challenging simulation scenarios. Abstract : We propose a novel monolithic pure SPH formulation to simulate fluids strongly coupled with rigid bodies. A new implicit particle‐based dry friction force for rigid‐rigid contacts is incorporated into the strong coupling between fluid and rigid bodies.